Perbandingan Upaya Pelemahan Terhadap Lembaga Antikorupsi Kpk Indonesia Dan Icac Hong Kong - Setyo Pratomo Baskoro, Narendro; Budi Eko Wardhani, Sri (CV RIFAINSTITUT, 2022)
The establishment of anti-corruption institutions in several countries does not guarantee that every country can be completely free from corruption, even efforts to weaken anti-corruption institutions such as the Indonesian KPK and Hong Kong ICAC have been and are still happening for the past few years. This study aims to examine how the weakening efforts were carried out, as well as the factors that led to the weakening of the two anti-corruption institutions. In this study using qualitative methods, the data collection techniques were obtained from documentation and from interviews with parties related to this research. The results of this study found that efforts to weaken anti-corruption institutions were carried out in various ways, namely if at the Indonesian KPK through regulatory means such as the revision of the 2019 KPK law which is still a matter of debate and controversy in the wider community, then another way is through criminalization and terror against KPK commissioners and employees by parties who are not happy with the existence of the KPK anti-corruption agency. At ICAC Hong Kong, this actually happened a lot from within the institution itself, such as several cases that dragged ICAC employees and commissioners and had resulted in the disruption of ICAC's performance in dealing with corruption cases. Efforts to weaken anti-corruption institutions can be avoided if there is political will from all parties, especially the Head of State, while consistently fully supporting the eradication of corruption and taking firm action against anyone who tries to weaken anti-corruption institutions